Pengetahuan Keluarga tentang Pencegahan Luka pada Penderita Diabetes Melitus - R, Rinawati; Batubara, Khairunnisa (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Diabetes mellitus (DM) is a metabolic disorder of carbohydrate, protein and fat resulting from a lack of balance between insulin availability and insulin demand. Diabetic foot wounds are categorized as chronic wounds that will not heal on their own, but with active treatment. So it is important for family members to know about the prevention of diabetic wounds in DM patients. The purpose of this study was to identify the description of knowledge in preventing wounds in patients with Diabetes Mellitus in family members of patients with Diabetes Mellitus. The type of research used is descriptive quantitative with 50 family members of DM patients as research respondents. The results showed that the largest percentage was adult age, namely 38 people (76%), the percentage of the largest gender was female as many as 37 people (74%), the percentage of marriage relationships had a large percentage of 28 people (56%), the percentage of the largest education level was high school as many as 23 people (46%), the largest category of knowledge is good enough knowledge as much 30 people (60%).